SOCIO-DEMOGRAPHIC PROFILE OF SEXUAL ASSAULT VICTIMS IN SOUT- EAST REGION OF RAJASTHAN BROUGHT FOR MEDICAL EXAMINATION AT SRG HOSPITAL, JHALAWAR (Journal of Forensic Medicine & Toxicology, 2025)
Approximately half of the world population comprises of women. Women are not safe in the world as well as in India today. Survey of WHO estimates that 10 to 69 per cent of women are physically harmed by male partner. Sex related crimes include sexual assault, rape and sexual abuse of children and trafficking of women for the purpose of sexual exploitation.This study aimed to assess the social and demographic profile of sexual offence cases brought for medical examination to identify the high-risk population. It is a retrospective study conducted on cases of alleged victims of sexual assault which are examined at SRG Hospital associated with Jhalawar medical college Jhalawar, Rajasthan during 01 January to 31 December 2023. Total 261 cases of alleged victim of sexual assault were observed. Our study showed that 191 cases were unmarried and 70 cases were married. We found that most affected age group of victims was below 18 years of age . Out of 261 cases , 66 (25.29%) cases belongs to age group of 12-16 years, 76 (29.12%) cases belongs to age group of 16-18 years and 7 (2.68%) cases belongs to less than 12 years of age. These findings indicated that young women are usually more at risk of offence of sexual assault.
Keywords: Victim; Sexual offences; Socio-demographic profile